2006
DOI: 10.1007/s10750-006-0094-3
|View full text |Cite
|
Sign up to set email alerts
|

European river plant communities: the importance of organic pollution and the usefulness of existing macrophyte metrics

Abstract: The macrophyte surveys undertaken as part of the EU-funded STAR project are a unique resource allowing aquatic plant communities to be studied at a Pan-European scale (211 stream sites with macrophytes in 14 countries). Using this dataset, we examined the influence of organic pollution in relation to other environmental correlates of river plant community variation across Europe. We examined the relationships between several existing macrophyte metrics and nutrient enrichment, and we also explored the possibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 24 publications
2
40
0
Order By: Relevance
“…This may seem surprising because the composition of assemblages of running-water macrophytes has often been regarded as strongly indicative of a river's nutrient status, especially in Europe (e.g. Ali et al 1999;Schneider and Melzer 2003;Szoszkiewicz et al 2006). However, some European studies have found only weak relationships between concentrations of nitrogen and phosphorus and macrophyte indices (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This may seem surprising because the composition of assemblages of running-water macrophytes has often been regarded as strongly indicative of a river's nutrient status, especially in Europe (e.g. Ali et al 1999;Schneider and Melzer 2003;Szoszkiewicz et al 2006). However, some European studies have found only weak relationships between concentrations of nitrogen and phosphorus and macrophyte indices (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have attempted to compare indicator scores of individual plant species across different river macrophyte assessment methods used within Europe (e.g. Szoszkiewicz et al, 2006a;Schneider, 2007), but such studies have focussed exclusively on trophic indices, have generally operated across types, or within very broad types (e.g. upland versus lowland) and have therefore avoided issues of benchmarking indices against concepts of minimal impact.…”
Section: Development Of a Common Metric For Intercalibrationmentioning
confidence: 99%
“…Biogeographical zone, catchment geology and stream hydrology establish the large-scale framework influencing occurrence and abundance of macrophytes (Lacoul & Freedman, 2006). Since most of these local factors are susceptible to anthropogenic alteration, macrophytes are potentially effective bioindicators that respond to various human pressures such as physical stream disturbance and alteration (Baattrup-Pedersen & Riis, 1999, 2004, river pollution (Schneider & Melzer, 2003;Hilton et al, 2006;Szoszkiewicz et al, 2006a), disruption of the riparian integrity (Ferreira et al, 2005) or general deterioration . In summary, these studies reveal some general patterns of community change under human influence: Anthropogenic disturbance fosters a decline in species richness especially of submerged macrophytes, the reduction of oligotrophic and large, slow growing species, leading to fragmentation of populations and rare species threatened by extinction, and favours macrophyte taxa with high growth capacity and efficient dispersal.…”
Section: Introductionmentioning
confidence: 99%
“…Four moss species: Brachythecium rivulare, Fontinalis antipyretica, Leptodictyum riparium and Platyhypnidium riparioides were chosen in the current study because: (i) they have high sensibility to different environmental stresses; (ii) they are strictly aquatic species; (iii) have wide distribution in Bulgaria; (iv) their taxonomy is relatively easy. (18). Platyhypnidium riparioides has score (5) only in MTR.…”
Section: Introductionmentioning
confidence: 99%